"Don't Take the Social Out of Social Work": The Social Work Career of Bessie Touzel (1904–1997). (August 2015) - Johnstone, Marjorie
Through an historical biographical lens, this article examines the career of an early Canadian social worker, Bessie Touzel (1904–1997). Touzel was a socialist feminist and practiced a left-leaning form of social work during the formative years of the profession. This was in tension with the earlier dominant ideas based on an imperial Anglo-Christian worldview. Two world wars, the Great Depression, and the establishment of the welfare state in Canada are the backdrop to contested ideas on the identity of the newly establishing female-dominated profession. As a woman in senior administration in early public social services, Touzel was a feminist pioneer with a vision of equal rights within a framework of universal rights. A closer look at her career illuminates not only the obstacles and challenges she faced as she strove to defend her personal social work values but also highlights the debates, which the profession struggled to reconcile.